Pengembangan Permainan Tebak Soal Dalam Power Point Untuk Meningkatkan Pengetahuan Kognitif Mahasiswa Mata Kuliah Pendidikan PKN Sd Program Studi PGSD STKIP Bina Insan Mandiri - Noviardani Kartika Prameswari (Proceedings of The ICECRS, 2018)
This study aims to develop the learning game of PKN elementary education courses of fun learning materials in the 2nd semester students. The use of guessing games through power points in learning can motivate students to high learning spirit. Using the game guess the problem in the group can know the cognitive learning outcomes of students when students are doing the game is accompanied by lecturers. This research is a device development research that used in game in the form of guess problem while test result of learning in the form of pretest and postest. Subjects in this study were 2nd semester students with 36 students. The result of survey documentation study during one semester shows that 2 semester students STKIP Bina Insan Mandiri still lack in critical thinking and innovative in following learning. This is because the giving strategy and teaching method belom maximally. Monotonous learning in the classroom becomes one of the factors of non-success in teaching and learning activities in the classroom. Thus in the course of education PKN SD fun learning materials will be given a game that can make students the spirit in following the learning in the classroom.